2014
DOI: 10.24126/jobrc.2014.8.1.289
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cellular immune response provoked by experimental infection with Cryptosporidium spp. in mice

Abstract: Experimental infection was induced in immunosupreesed and non-immunosupressed mice using inoculation of two different Cryptosporidium spp. isolates: faecal origin and river water origin; then the infectivity rate and cellular immunological status were examined in these groups of mice. The results indicated that these two isolates induced experimental infection in immunosuppressed and non-immunosuppressed mice with no significant differences in infectivity rate between groups. Immunosuppressed mice infected wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The Same result was obtained from Al-Zarkoushi and Al-Zubaidi (2021b) on quails intestinal tissue that was infected with coccidian. Al-Warid et al (2014) conclouded that lymphocyte and phagocytosis are good indicter to evaluate the cellular immune response in experimentally mice with Cryptosporidium spp. This result disagreed with Cui et al (2018) who found numbers of C. avium oocysts cover the epithelial cell of the small intestine without any pathological change in the epithelial cell.…”
Section: Histopathological Examinationmentioning
confidence: 99%
“…The Same result was obtained from Al-Zarkoushi and Al-Zubaidi (2021b) on quails intestinal tissue that was infected with coccidian. Al-Warid et al (2014) conclouded that lymphocyte and phagocytosis are good indicter to evaluate the cellular immune response in experimentally mice with Cryptosporidium spp. This result disagreed with Cui et al (2018) who found numbers of C. avium oocysts cover the epithelial cell of the small intestine without any pathological change in the epithelial cell.…”
Section: Histopathological Examinationmentioning
confidence: 99%